Noongar Mambara Bakitj - Scott, Kim; Roberts, L. (UWA Publishing, 2011)
Noongar Mambara Bakitj was created as part of an Indigenous language recovery project led by Kim Scott and the Wirlomin Noongar Language and Stories Project.